Application of fuzzy AHP on the selection of online shopping platform in Malaysia / Siti Nurmaisarah Zakaria and Khairu Azlan Abd Aziz - Zakaria, Siti Nurmaisarah; Abd Aziz, Khairu Azlan (College of Computing, Informatics and Media, UiTM Perlis, 2023)
E-commerce, popular known as an online shopping platform is a digital platform that helped ease people buying or selling without having to go to a physical store. There are numerous kinds of these platforms in the whole world, but only a few are supporting shipping to Malaysia like Shopee, Lazada, Carousell, et cetera. However, users sometimes feel it difficult to choose a preferred online shopping platform, since there are platforms with better navigation, but not many choices of products, and so on. Hence, this study aims to determine the optimal factors and sub-factors that influence users in choosing an online shopping platform in Malaysia and to rank those factors and sub-factors. The fuzzy Analytic Hierarchy Process has been used as the method to achieve the objectives of this research by ranking the four factors which are user-friendly, trusted, price and promotion, and responsive, with three sub-factors for each factor. This study used primary data collected by distributing questionnaires to two experts, an online marketer from a business company and a lecturer with marketing expertise from UiTM Arau, Perlis. The findings show that price and promotion is the factor that influences users the most when choosing an online shopping platform whose normalised weight is 0.5083. For the major sub-factors, sales promotion benefit has a normalised weight of 0.2350. In conclusion, the Fuzzy AHP method can help researchers to rank all the factors and sub-factors with accuracy, and help users determine a suitable online shopping platform for them to use.